The Preservation of Balinese Spoken Language at the Ngaben and Potong Gigi Event - Made Sumiati Astiti; Ratu Wardarita; Yessi Fitriani (Yayasan Karinosseff Muda Indonesia, 2020)
This study aimed to describe the preservation of Balinese spoken language in the Ngaben and Potong Gigi events in Nusa Raya Village, Belitang III District, East OKU Regency. The method used in this research was a descriptive qualitative method. Data collection techniques in this study used observation and recording techniques. The results showed that the preservation of Balinese spoken language at the Ngaben event consisting of (1) the family domain, (2) the work background domain, (3) the religion domain, (4) the customs domain, while the retention of Balinese spoken language at the Potong Gigi event consisted of (1) Sangkep activity / Traditional meeting, (2) the core activities of Metatah/Potong Gigi remained very well. Based on the results of the study, it can be concluded that the preservation of Balinese spoken language in the Ngaben and Potong Gigi event in Nusa Raya Village, Belitang III District still survives well.